Correlation of Vitamin D with Monocytes and Lymphocytes in Care Takers of Tuberculosis Patients - Kiran Namoos, Anila Jaleel, Sadaf Saleem Uppal, Samar Asim, Rukhshan Khursheed, Arsalan Saleem Chughtai, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Close relatives of tuberculosis patients may be at increased risk of developing the disease as they are in close contact with them Objectives: A cross-sectional research was conducted to determine correlation of Vitamin D with monocytes and lymphocytes in individuals with active tuberculosis as well as their care takers. Material and Methods: Total of 83 subjects was divided into three groups. Of the 83 participants, 31 had active tuberculosis, while 31 were adult family members who lived with and looked after the patients. 21 healthy age matched individuals were chosen to form the control group. SWISS Max analyzer was used to evaluate the levels of lymphocytes and monocytes in the blood and Vitamin D was measured by ELISA. Results: Vitamin D levels and monocyte lymphocyte count in the three groups showed substantial variation. The patient's monocyte and lymphocyte count showed a statistically significant correlation. However there was non-significant correlation of vitamin D with both monocyte and lymphocyte. Conclusion: Caretakers of active tuberculosis patients showed increased levels of circulating monocytes, lymphocytes as well as lower vitamin D levels with increased risk of developing tuberculosis. Keywords: care taker, tuberculosis, vitamin D, monocyte and lymphocyte